THE EFFECT OF H5P-BASED LUMI EDUCATION ON ISLAMIC CULTURAL HISTORY LEARNING OUTCOMES OF GRADE V MI STUDENTS - Nurun Nafisah Indah Qomari; Ruqoyyah Nafisah (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2026)
The teaching of Islamic Cultural History (SKI) in madrasah settings continues to face persistent challenges, including limited interactive media, predominantly narrative instructional materials, and low student engagement. The topic of the Caliphate of Ali ibn Abi Talib, in particular, demands media that can present historical figures, sequences of events, and exemplary values in a more engaging manner. This study investigates the effect of H5P-based Lumi Education on the learning outcomes of fifth-grade students at MI Darul Hikmah Al-Fatimiyah. Employing a quantitative approach with a pre-experimental one-group pretest-posttest design, the study involved 24 students. Data were collected through pretest and posttest instruments and analyzed using descriptive statistics, the Shapiro-Wilk normality test, and the Wilcoxon Signed-Rank Test due to non-normal data distribution. Results indicated that the mean score increased from 86.04 at pretest to 94.79 at posttest, with the Wilcoxon test yielding a statistically significant difference (p = 0.001). A rank-biserial correlation of 0.860 indicated a large effect size, while the Hodges-Lehmann Estimate suggested a typical improvement of approximately 10 points. These findings demonstrate that H5P-based Lumi Education positively contributes to SKI learning outcomes, though interpretations should remain cautious given the single-group design, limited sample size, and restricted content scope.